Battery test innovation for table tennis skills - Widodo, H.; Tomoliyus; Alim, A. (Journal of Human Sport & Exercise, 2024)
Table tennis is a sport that requires skill as a determining factor in athletes competing at the elite level. This is inseparable from tests and measurements of athlete skills. This study's objective was to evaluate the battery test's content validity for table tennis skills. This study uses a mixed method of qualitative and quantitative, explorative sequential model design. The Delphi technique was utilized to collect the study data, with the subjects including thirty players of table tennis as well as four professional specialists in the sport as well as three academic experts. This study used an instrument with a rating scale of one to five. Furthermore, the data obtained were analysed using the Aiken formula. The qualitative results explained that the dominant variables of the battery test for table tennis skills that need to be measured included forehand drive, backhand drive, forehand topspin, backhand topspin, backspin service, and topspin service. The results showed that the table tennis skills battery test obtained a value of V = 0.969 for the first aspect, the second aspect obtained a value of V = 0.969, the third aspect obtained a value of V = 0.969, the fourth aspect obtained a value of V = 0.969, the fifth aspect obtained a value of V = 0.906, the sixth aspect obtained a value of V = 0.875, and the seventh aspect obtained a value of V = 0.844. Furthermore, the ICC results show that the average points of each athlete are categorized as good. Based on these results, the table tennis skills battery test has high content validity and has good reliability so the table tennis skills battery test can be used to measure table tennis skills.